Se-Regulated MnS Porous Nanocubes Encapsulated in Carbon Nanofibers as High-Performance Anode for Sodium-Ion Batteries - Liang, Puwu; Pan, Duo; Hu, Xiang; Yang, Ke R.; Liu, Yangjie; Huo, Zijing; Bo, Zheng; Xu, Lihong; Xu, Junhua; Wen, Zhenhai (Nano-Micro Letters, 2025)
Manganese-based chalcogenides have significant potential as anodes for sodium-ion batteries (SIBs) due to their high theoretical specific capacity, abundant natural reserves, and environmental friendliness. However, their application is hindered by poor cycling stability, resulting from severe volume changes during cycling and slow reaction kinetics due to their complex crystal structure. Here, an efficient and straightforward strategy was employed to in-situ encapsulate single-phase porous nanocubic MnS0.5Se0.5 into carbon nanofibers using electrospinning and the hard template method, thus forming a necklace-like porous MnS0.5Se0.5-carbon nanofiber composite (MnS0.5Se0.5@N-CNF). The introduction of Se significantly impacts both the composition and microstructure of MnS0.5Se0.5, including lattice distortion that generates additional defects, optimization of chemical bonds, and a nano-spatially confined design. In situ/ex-situ characterization and density functional theory calculations verified that this MnS0.5Se0.5@N-CNF alleviates the volume expansion and facilitates the transfer of Na+/electron. As expected, MnS0.5Se0.5@N-CNF anode demonstrates excellent sodium storage performance, characterized by high initial Coulombic efficiency (90.8%), high-rate capability (370.5 mAh g−1 at 10 A g−1) and long durability (over 5000 cycles at 5 A g−1). The MnS0.5Se0.5@N-CNF //NVP@C full cell, assembled with MnS0.5Se0.5@N-CNF as anode and Na3V2(PO4)3@C as cathode, exhibits a high energy density of 254 Wh kg−1 can be provided. This work presents a novel strategy to optimize the design of anode materials through structural engineering and Se substitution, while also elucidating the underlying reaction mechanisms. Highlights: 1 We have developed an efficient and scalable strategy to prepare a single-phase ternary MnS0.5Se0.5-carbon nanofiber composite with a defect-rich microstructure. 2 The Na+ storage mechanism of manganese-based sulfides after the incorporation of Se was thoroughly investigated, through systematic electrochemical characterization combined with theoretical calculations. 3 The MnS0.5Se0.5@N-carbon nanofiber composite, used as an anode, exhibits excellent reversible capacity, rate capability, and cycling stability in sodium-ion batteries.